2011
DOI: 10.1002/pros.21358
|View full text |Cite
|
Sign up to set email alerts
|

The expression of tousled kinases in CaP cell lines and its relation to radiation response and DSB repair

Abstract: TLKs appear to be intimately linked to the pattern of resistance to DNA damage, and specifically DSBs, a finding that was not reported before for any cell lines, and certainly not systematically for human prostate cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Silencing RNA-mediated suppression of TLKs eventually kills all cells (normal or cancer) even without IR or RMT. 11,30 These are essential proteins as chaperones, while the kinase activity seems less critical and needed for more complex and specialized functions, as shown here. In fact, we could produce a stable cell line of normal mammary fibroblasts expressing a TLK1-KD mutant (in the presence of wild-type endogenous TLKs), but we also used siRNA to complement the work, which arrested the cells and then killed them.…”
Section: Discussionmentioning
confidence: 59%
“…Silencing RNA-mediated suppression of TLKs eventually kills all cells (normal or cancer) even without IR or RMT. 11,30 These are essential proteins as chaperones, while the kinase activity seems less critical and needed for more complex and specialized functions, as shown here. In fact, we could produce a stable cell line of normal mammary fibroblasts expressing a TLK1-KD mutant (in the presence of wild-type endogenous TLKs), but we also used siRNA to complement the work, which arrested the cells and then killed them.…”
Section: Discussionmentioning
confidence: 59%
“…Improper regulation of this process caused by increased TLK activity (or deficient TLK inhibition) could promote cell survival after DNA damage, which in turn could lead to increased mutation rates, genomic instability and radioresistance. Several human cancers have been identified that feature mutations in the kinase domain of TLK1 [5862], and high TLK1 expression levels correlate with radioresistance [63,64] thus raising the possibility that TLK1 is an oncogene and potential therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that TLKs are overexpressed likely renders tumor cells more dependent on these kinases than normal tissues and, hence, their preferential TLK-targeted killing. In contrast to BCA, in the most common human CaP cell lines, only one or the other TLK gene is expressed [71], although typically at high level—we do not have the story yet for the analysis of patient samples. The significance of the TLK/Rad9 axis is perhaps even greater for prostate cancer for which several studies have implicated the critical role of Rad9 in disease progression and prognosis.…”
Section: Tlks In Man As Guardians Of Genome Stability and Their mentioning
confidence: 99%